Upadacitinib for refractory Behçet’s disease with myelodysplastic syndrome and trisomy 8/9: a case report and mechanistic insights - Wang, Yukai; Tian, Feng; Li, Hui (Frontiers in Immunology, 2025)
BackgroundBehçet’s disease (BD), a multisystemic inflammatory disorder with genetic predisposition, is frequently complicated by myelodysplastic syndrome (MDS), particularly in cases harboring trisomy 8. Patients with refractory BD-MDS exhibit poor responses to conventional therapies, including glucocorticoids and TNF-α inhibitors, underscoring the need for novel therapeutic strategies. Janus kinase (JAK) inhibitors, which target cytokine-driven inflammation, represent a promising approach; however, clinical evidence in genetically complex BD-MDS cases remains limited.Case presentationWe report a 29-year-old female with refractory intestinal BD, MDS, and dual trisomy 8/9, who presented with recurrent ulcers, thrombocytopenia, and ileocolonic resection due to perforation. Despite sequential therapies (thalidomide, prednisolone, and infliximab), disease progression persisted. Initiation of upadacitinib (45 mg/day), a selective JAK1 inhibitor, resulted in symptom resolution within one week and complete mucosal healing confirmed by colonoscopy at three months. Dose reduction to 15 mg/day led to disease relapse, while maintenance at 30 mg/day sustained remission over 12 months.MethodsImmunohistochemical (IHC) analysis of intestinal specimens from the patient and three additional BD cases revealed robust phosphorylation of JAK1 and STAT3 in mucosal epithelium, stroma, and inflammatory infiltrates, particularly within occluded submucosal vessels. These findings mechanistically implicate JAK-STAT hyperactivation in BD-associated vascular pathology.ConclusionThis study highlights the efficacy of upadacitinib in managing refractory BD with MDS and dual trisomy 8/9, a genetically complex phenotype. The dose-dependent response underscores the importance of tailored dosing strategies. Our mechanistic data further support JAK inhibition as a viable therapeutic alternative for TNF-α inhibitor-resistant BD. These results warrant validation through randomized controlled trials to optimize therapeutic protocols for similar high-risk populations.